An investigative study into the performance of procedural controllers in simulators - Muhammed Nasiruddin Bin Rahmat (2017)
The present air traffic is expected to reached its capacity limit and thus may not be able to accommodate the air traffic that is expected to double in the next 15 years. This is due to the constantly growing public demand for air travel. Airspace would likely be more complex and the amount of work expected from air traffic controllers will be increased, affecting their performance. Such is more prominent for procedural controllers, as they need to continue to monitor multiple airspace despite this increase in complexity. These may further worsen the problem of blind-sidedness of procedural controller adding unnecessary workload as a result. With that, the objective of this project is to introduce an automated system that helps to reduce blind-sidedness of procedural controllers by providing a reliable and consistent data exchange between procedural controller. As such, the distribution of task of procedural controllers and the possibility of reducing the number of routine task is investigated. A mock-up of an electronic flight strip that incorporates this automated was also done to illustrate the contrast of having the combined system. Test results show that through a combined system, there will be a potential savings valued in terms of time from reducing the task and safety can be enhanced through minimizing human error.